Program evaluation of a virtual physical activity program for individuals with disabilities - Matthews, Nikki; Seaman, Roxanne; Bremer, Emily (Frontiers in Sports and Active Living, 2023)
Regular physical activity is important for positive health outcomes yet, most individuals do not meet physical activity guidelines. Recent studies show that one in five Canadians aged 15 or older have one or more disabilities, yet as a population, individuals with disabilities are 16-62% less likely to meet physical activity guidelines. The COVID-19 pandemic created additional barriers to physical activity participation as lockdowns prevented in-person programming. In response to the pandemic, the Acadia University Sensory Motor Instructional Leadership Experience (S.M.I.L.E.) Program shifted its programming to a virtual platform; however, there was little research to guide its creation, implementation, or expected outcomes. Thus, this pilot study explored program feasibility and impact on physical activity and physical literacy. A mixed methods case study approach was used for this project. Virtual S.M.I.L.E. took place over eight weeks in the fall of 2020. Programming consisted of three live Zoom sessions facilitated by trained program leaders, and eight weeks of at-home activity guides for participants to complete on their own time. Demographic data, physical literacy (PLAYself), and physical activity (IPAQ-A) data were collected using caregiver pre-and post-programming surveys. Throughout programming, weekly check-in surveys were sent to reflect on the previous week of programming. After the eight weeks of programming were complete, caregiver and leader interviews were conducted to understand both program implementation and performance perspectives. Results indicated that participants’ (N=15, Mage=20.4 years) overall physical literacy and physical activity did not change; however, there was a decrease in the cognitive domain of physical literacy (p=0.03). Caregiver and leader interviews highlighted five main themes following the virtual programming: (a) Virtual impact on programming; (b) Programming impact on social and motor goals; (c) Impact of program design; (d) Impact on physical activity; and (e) Program feasibility for families. Results from this pilot study suggest that physical literacy and physical activity levels were generally maintained throughout programming and caregivers indicated several social and activity benefits. Future work includes program modifications and further evaluation of virtual adapted physical activity programming to improve the physical literacy of individuals with disabilities.